2021
DOI: 10.4070/kcj.2020.0542
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Management Status of Younger Hypertensive Population in Korea

Abstract: May Measurement Month (MMM) is an initiative of the International Society of Hypertension with a primary goal of improving hypertension (HTN) awareness by measuring blood pressure (BP) in millions of people worldwide. MMM 2019 Korea, the first MMM campaign held in Korea, reported that one-third of the participants had uncontrolled BP. Remarkably, the awareness rate in young hypertensive participants was less than 10%. While awareness, treatment, and control of hypertension have improved remarkably, the younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The awareness rates of HT have improved little in younger adults from 10% in 1998 to 15% in 2019, which is in sharp contrast to older adults, whose awareness rates have steadily increased from 30 to 80% in the same period in Korea [ 3 ]. As a result, only 24% of young hypertensive patients seek medical care at least once and among them, only one-third are regularly treated [ 2 ]. Similarly, the US NHANES 2013–2014 data reported an awareness rate of 74.7%, a treatment rate of 50%, and a control rate of 40.2% among young adults with HT, which was lower than that of hypertensive patients in the all-age group (84.4%, 74.7%, and 53.…”
Section: Epidemiology Of Hypertension Among Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The awareness rates of HT have improved little in younger adults from 10% in 1998 to 15% in 2019, which is in sharp contrast to older adults, whose awareness rates have steadily increased from 30 to 80% in the same period in Korea [ 3 ]. As a result, only 24% of young hypertensive patients seek medical care at least once and among them, only one-third are regularly treated [ 2 ]. Similarly, the US NHANES 2013–2014 data reported an awareness rate of 74.7%, a treatment rate of 50%, and a control rate of 40.2% among young adults with HT, which was lower than that of hypertensive patients in the all-age group (84.4%, 74.7%, and 53.…”
Section: Epidemiology Of Hypertension Among Young Adultsmentioning
confidence: 99%
“…Hypertension (HT) is considered a disease of older adults, due to which, cardiovascular risk assessment and active control have been suboptimal for younger hypertensive populations [ 1 ]. In South Korea, approximately 90% of the young hypertensive population is unaware that they have HT [ 2 ] and only 24% of them are treated [ 3 ]. Although national guidelines have been implemented adequately in older hypertensive patients, several recent meta-analyses and reviews have reported a low degree of compliance with these guidelines in young hypertensive patients [ 4 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although hypertension prevalence is low in those in the 3rd to 4th decade of life, they showed a low rate of awareness in hypertension. 25) 26) With a PPG App in their smartwatch, people need to measure BP using standard devices only every 4 weeks for re-calibration. For the remainder of the time, the smartwatch will track and report BP values automatically.…”
Section: Pitfalls For Daily Clinical Practice Usementioning
confidence: 99%
“…For example, high blood pressure is generally related to lifestyle habits such as excessive sodium intake, obesity, smoking, and drinking. 5) 13) 14) Therefore, the optimal blood pressure can be achieved through lifestyle modification, but this depends on patients’ sustained self-management. 5) An app that measures and monitors body weight and provides customized fitness or training plans for patients with high blood pressure leads to lifestyle changes and provides secondary precautions for patients with cardiovascular disease.…”
Section: Concept Of Digital Therapeuticsmentioning
confidence: 99%